2020
DOI: 10.1111/vox.12982
|View full text |Cite
|
Sign up to set email alerts
|

Non‐phthalate plasticizer DEHT preserves adequate blood component quality during storage in PVC blood bags

Abstract: Background and objectives Commercial blood bags are predominantly made of polyvinyl chloride (PVC) plasticized with di(2‐ethylhexyl) phthalate (DEHP). DEHP is favourable for storage of red blood cells (RBC). Historically, removal of DEHP from blood bags has been linked to unacceptable haemolysis levels. Oncoming regulatory restrictions for DEHP due to toxicity concerns increase the urgency to replace DEHP without compromising RBC quality. Di(2‐ethylhexyl) terephthalate (DEHT) is one suggested substitute. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 34 publications
(43 reference statements)
4
36
0
Order By: Relevance
“…RMVs are shed from the RBC membrane as part of the storage lesion process, as ROS increases and antioxidants and ATP are depleted [2]. In this study, the generation of RMVs had similar but earlier onset than in non‐irradiated units [23]. This is likely attributed to increased ROS generation caused by irradiation, both directly and through the positive feedback loop provided by the haemolysis‐induced increase of free haemoglobin [11, 12].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…RMVs are shed from the RBC membrane as part of the storage lesion process, as ROS increases and antioxidants and ATP are depleted [2]. In this study, the generation of RMVs had similar but earlier onset than in non‐irradiated units [23]. This is likely attributed to increased ROS generation caused by irradiation, both directly and through the positive feedback loop provided by the haemolysis‐induced increase of free haemoglobin [11, 12].…”
Section: Discussionmentioning
confidence: 82%
“…Membrane proteins of ATPase character control the asymmetry between the inner and outer leaflet, and when ATP levels decrease, there is a progressive translocation of phosphatidylserine to the outer leaflet [27], where it plays a signalling role for phagocytosis [28]. The literature is ambiguous as to whether the percentage of phosphatidylserine positive RMVs from non‐irradiated RBCs increases during storage or not; several studies, our own previous study included, seem to suggest that it does not [23, 29, 30]. However, as irradiation induces increased oxidizing damage to membrane‐bound proteins [11, 12], it may be hypothesized that the observed increase in the frequency of RMVs exposing phosphatidylserine may be a consequence of irradiation damage.…”
Section: Discussionmentioning
confidence: 99%
“…for DEHT blood bags with PAGGS-M storage solution; however, these values were still higher compared to the values for DEHP blood bags with SAGM storage solution throughout the 49-day RBC storage period [10]. Similarly, Graminske et al reported higher haemolysis levels for DEHT with PAGGS-M compared to DEHP with AS-1 at the end of the 42-day storage period [11].…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, shelf-life can be shortened to provide RBC products with lower haemolysis. Current non-DEHP alternatives result in increased haemolysis during blood storage, requiring reconsideration of the RBC shelf-life [9][10][11][12]. In order to mitigate this impact, research is moving towards 'alternative combinations' of new plasticizers with new RBC storage solutions [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation